Lenalidomide improves NKG2D-based CAR-T cell activity against colorectal cancer cells invitro - Mahdi Zarei; Shahriyar Abdoli; Touraj Farazmandfar; Majid Shahbazi (Heliyon, 2023)
Introduction: Although CAR-based immunotherapy is viewed as a promising treatment for tumors, particularly hematological malignancies, solid tumors can pose challenges. It has been suggested that the immunomodulatory medication Lenalidomide (LEN) may increase the effectiveness of CAR T cells in the treatment of solid tumors. The purpose of our study was to investigate the effect of NKG2D-based CAR T cell therapy on colorectal cancer cell lines, and then we assessed combinatorial therapy using NKG2D CAR T cells and lenalidomide in vitro. Methods and results: To prepare NKG2D CAR T cells, a second-generation NKG2D-CAR construct was designed and transfected into the T cells using a lentiviral system. The NKG2D CAR T cells showed significantly higher cytotoxic activity against colorectal cancer cell lines, HCT116 and SW480, compared to untransduced T cells. In addition, our data demonstrated that the cytotoxicity and cytokine secretion of NKG2D CAR T cells significantly increased in the presence of higher doses of lenalidomide. Conclusions: The study findings suggest that combinational therapy, utilizing NKG2D-based CAR T cells and lenalidomide, has a high potential for effectively eliminating tumor cells in vitro.